A novel member of the rho family of small GTP-binding proteins is specifically required for cytokinesis (The Rockefeller University Press, 1996)
Several members of the rho/rac family of small GTP-binding proteins are known to regulate the distribution of the actin cytoskeleton in various subcellular processes. We describe here a novel rac protein, racE, which is specifically required for cytokinesis, an actomyosin-mediated process. The racE gene was isolated in a molecular genetic screen devised to isolate genes required for cytokinesis in Dictyostelium. Phenotypic characterization of racE mutants revealed that racE is not essential for any other cell motility event, including phagocytosis, chemotaxis, capping, or development. Our data provide the first genetic evidence for the essential requirement of a rho-like protein, specifically in cytokinesis, and suggest a role for these proteins in coordinating cytokinesis with the mitotic events of the cell cycle.